Distal hypospadias repair in children: 8 years of experience - Özel, Ş. Kerem; Kazez, Ahmet; Bakal, Ünal (Fırat University, 2007)
Objectives: Distally located urethral mea is the most common type of hypospadias. Different surgical techniques have been defined although main principles were unchanged. Aim of this study was to evaluate the outcomes of patients treated for distal hypospadias. Materials and Methods: Medical records of 39 distal hypospadiac patients of the last eight years were reviewed. Age, mea localization, type of operation, stenting time, postoperative fistula and stenosis development were evaluated. Stenting time after distal hypospadias repair was compared between its different types. The groups were compared with one-way ANOVA test. Results: Mean age of the patients was 5.7±3.2 years of age. Subcoronal hypopadias was more frequent (53.8%). In glanular type MAGPI, in coronal mostly MAGPI (75%), in subcoronal mostly Mathieu (81%), in distal penile only Mathieu operations were preferred. Stenting time was 2±2.7 days in glanular, 4.9±2.2 days in coronal, 6.9±2.6 days in subcoronal and 6.5±0.6 days in distal penile type. Statistical analysis revealed significant increased stenting time after repair of subcoronal hypospadias in contrast to other types except for distal penile (p

Amaç: Distal yerleşimli üretral mea, en sık karşılaşılan hipospadias tipidir. Temel prensiplerin değişmemesine rağmen onarım için çok farklı yöntemler tarif edilmiştir. Bu çalışmada kliniğimizde tedavi edilen distal hipospadiaslı olguların irdelenmesi amaçlanmıştır. Gereç ve Yöntem: Son sekiz yılda tedavi edilen toplam 39 distal hipospadiaslı olgunun kayıtları incelendi. Hastaların yaşı, mea lokalizasyonu, ameliyat yöntemi, stent süresi, ameliyat sonrası fistül ve darlık gelişimi değerlendirildi. Distal hipospadias onarımı sonrasında stent bırakılma süreleri kendi içlerindeki tiplerine göre karşılaştırıldı. Gruplar, one-way ANOVA testi ile karşılaştırıldı. Bulgular: Değerlendirmeye alınan olguların yaşları ortalama 5.7±3.2 yıl idi. Bu grup içinde en sık subkoronal hipospadiasın olduğu görüldü (%53.8). Glanüler tipte MAGPI, koronal tipte çoğunlukla MAGPI (%75), subkoronal tipte çoğunlukla Mathieu (%81), distal penil tipte ise sadece Mathieu ameliyatının tercih edildiği belirlendi. Stent bırakılma süreleri glanüler tipte; 2±2.7 gün, koronal tipte 4.9±2.2 gün, subkoronal tipte 6.9±2.6 gün ve distal penil tipte 6.5±0.6 gün idi. Yapılan karşılaştırmada subkoronal onarımda stentin distal penil hariç diğer gruplara göre, daha uzun tutulduğu saptandı (p
Çocuklarda Distal Hipospadias Onarımı: 8 Yıllık Deneyim